Five nights at Freddy's 2 [videorecording (DVD)] - Cawthon, Scott, 1971-; Hutcherson, Josh; Lail, Elizabeth; Rubio, Piper; Grace, Mckenna, 2006-; Carter, Freddy; Crane, Theodus; Briones, Teo; Knight, Wayne; Ulrich, Skeet; Lillard, Matthew, 1970- (Universal Studios, 2026)
One year has passed since the supernatural nightmare at Freddy Fazbear's Pizza. The stories about what transpired there have been twisted into a campy local legend, inspiring the town's first ever Fazfest. Former security guard Mike and police officer Vanessa have kept the truth from Mike's 11-year-old sister, Abby, concerning the fate of her animatronic friends. But when Abby sneaks out to reconnect with Freddy, Bonnie, Chica, and Foxy, it will set into motion a terrifying series of events, revealing dark secrets about the true origin of Freddy's, and unleashing a long-forgotten horror hidden away for decades.